Helium nanodroplet infrared spectroscopy of oxazole-(water)n (n = 1,2) clusters - Tarun Kumar Roy (AIP Publishing LLC, 2021)
The mass-selective infrared (IR) spectra of oxazole-(D2O)n≤2 complexes embedded in helium droplets are recorded in the spectral range of 2565–2800 cm−1. The experimental IR spectra are assigned by comparing with quantum chemical calculations at the MP2/6-311++G(d,p) level of theory. Here, we show that in the case of the 1:1 oxazole-D2O dimer, the water molecule binds to the N atom of the heterocyclic ring via a N⋯DO hydrogen bond (H-bond). However, in the oxazole-(D2O)2 trimer, the water dimer forms N⋯DO and CH⋯O H-bonds with the N atom and adjacent CH group, respectively, leading to the formation of a seven-membered ring. We compare these results with those of our recently reported isoxazole-(water)n≤2 complexes to demonstrate differences in the hydration motif of these two structural isomers.